Correlation of biomechanical properties and greyscale image of articular cartilage using low-field Magnetic Resonance Imaging - Ibramsa, Rizwana Seeni (2022)
Osteoarthritis (OA) is a degenerative disease which is associated with the articular cartilage in the synovial joint. As the disease progresses, it changes the macromolecular structure inside the cartilage tissue and alters the biomechanical properties. Hence, the ability to detect the disease at its earliest stage is crucial for early intervention of the disease. The OA is clinically diagnosed using magnetic resonance imaging (MRI) by examining the morphology of the articular cartilage and the geometrical data of the synovial joint. However, most of the diagnoses were performed when this disease is already progressed into advanced stage. At early stage of OA, the biomechanical properties start to show noticeable change. Although studies were conducted to correlate between the biomechanical properties of cartilage and MRI image, high-field MRI was utilised to produce the cartilage image. Therefore, this study aimed to investigate the potential use of low-field MRI to monitor the biomechanical properties of articular cartilage. This includes to determine the greyscale of low-field MRI image, characterise the biomechanical properties of articular cartilage and finally to observe the correlation between the greyscale and biomechanical properties of articular cartilage from both fresh and frozen joint specimen. Intact hip joints of bovine were scanned using 0.18 T MRI. The images of cartilage were characterised based on the intensity of the greyscale. Creep indentation test was then conducted on the cartilage specimens and subsequently the indentation test was simulated using finite element method. The biomechanical properties of elastic modulus and permeability of cartilage were characterised by incorporating the experimental data from the indentation test with the computational finite element model. The average elastic modulus was found to be 1.70 ± 0.65 MPa while the permeability was 0.53 ± 0.25 ×10-15 m4/Ns. Further correlation analyses were performed to examine the relationship between the greyscale of MRI image and biomechanical properties of elastic modulus and permeability of the cartilage. Good correlation was found between the cartilage greyscale and cartilage biphasic elastic modulus (r= 0.85) and a moderate correlation with negative value was observed between the cartilage greyscale and cartilage permeability (r= -0.51). Whereas in frozen condition, moderate correlation was found between the cartilage greyscale and cartilage biphasic elastic modulus (r= 0.66) and a moderate correlation with negative value was observed between the cartilage greyscale and cartilage permeability (r= -0.56). Hence, present results indicate that the low-field MRI have the potential to provide reliable data to determine the condition of articular cartilage. It could be further developed to serve as an early intervention of OA disease.